2020
DOI: 10.3390/molecules25071676
|View full text |Cite
|
Sign up to set email alerts
|

Toxic, Radical Scavenging, and Antifungal Activity of Rhododendron tomentosum H. Essential Oils

Abstract: The chemical composition of eight (seven shoot and one inflorescence) essential oils (EOs) of Rh. tomentosum H. plants growing in Eastern Lithuania is reported. The plant material was collected during different phases of vegetation (from April to October). The oils were obtained by hydrodistillation from air-dried aerial parts (leaves and inflorescences). In total, up to 70 compounds were identified by GC−MS and GC (flame-ionization detector, FID); they comprised 91.0 ± 4.7%–96.2 ± 3.1% of the oil content. Ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 51 publications
0
34
0
2
Order By: Relevance
“…Rhododendron tomentosum H. (ex Ledum palustre L.) plant material, the essential oils of which are already investigated [13,[31][32][33][34], was collected mostly in the Eastern part of the country (Rokiškis, Utena, Vilnius and Šalčininkai districts), and in one study [16] a sampling site was not indicated (Fig. 1).…”
Section: Chemical Variability Of the Essential Oils Of Marsh Rosemarymentioning
confidence: 99%
See 4 more Smart Citations
“…Rhododendron tomentosum H. (ex Ledum palustre L.) plant material, the essential oils of which are already investigated [13,[31][32][33][34], was collected mostly in the Eastern part of the country (Rokiškis, Utena, Vilnius and Šalčininkai districts), and in one study [16] a sampling site was not indicated (Fig. 1).…”
Section: Chemical Variability Of the Essential Oils Of Marsh Rosemarymentioning
confidence: 99%
“…Anticancer in vitro, using mouse leukemia cells L1210 [5] Anticancer in vitro, using human lympho-blastoid Raji cells [6] Analgesic, using model of acetic acid-induced writhing response in mice [7] Antibacterial in vitro, by broth dilution method, against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae [8] Antidiabetic in vitro, using C2C12 murine skeletal myoblasts and the 3T3-L1 murine preadipocyte cell lines [9] Antidiabetic in vitro, using Caco-2/15 cells; western blot analysis in vivo. Rats, oral glucose tolerance test [10] Antifungal, against Aspergillus niger, Candida albicans, Microsporum canis, Trichophyton rubrum and Trichophyton mentagrophytes [11] Antifungal in vitro, by microbroth dilution method, against Cryptococcus neoformans, Saccharomyces cerevisiae, Aspergillus niger and Candida albicans [12] Antifungal, using agar disc diffusion assay, against Candida parapsilosis [13] Antifungal, using mediated amperometry at Saccharomyces cerevisiae-modified electrodes [13] Antifungicidal, by agar-diffusion method, against Trichoderma harzianum and Penicillium cyclopium [14,15] Anti-inflammatory, by model of lambda-carrageenan-induced paw edema in mice [7] Anti-inflammatory in vivo, using tests of carrageenan-induced edema in rats [8] Anti-inflammatory, using tests of subcutaneous carrageenan injection-induced hind paw oedema in rats [16] Anti-inflammatory in vitro, by prostaglandin biosynthesis assay; PAF-induced exocytosis [17] Antimicrobial Variuos parts of the plant -all aerial parts or separated shoots, inflorescences and seeds -have been chosen for the oils preparation. Plant material was dried at room temperature (20-25°C); different plant organs were separated before drying.…”
Section: Chemical Variability Of the Essential Oils Of Marsh Rosemarymentioning
confidence: 99%
See 3 more Smart Citations